2020
DOI: 10.32819/2020.83030
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of application of inorganic and nanopreparations of selenium and probiotics for growing young quails

Abstract: Modern industrial poultry farming occupies a leading position in the production of dietary foods, for which it is appropriate to use biologically active substances and probiotics. The study compared the effectiveness of compound feed with the addition of sodium selenite, bio-nano-selenium and L. plantarum in terms of body weight, weight gain, feed consumption and safety of experimental quail. The quails of the Pharaoh meat breed were kept in the vivarium of Bila Tserkva National Agrarian University and by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(51 reference statements)
0
8
1
Order By: Relevance
“…Previous authors considered that the use of high inorganic selenium doses in the diet of quails be limited due to the possible toxic effects. (13) However, our results showed that an amount of sodium-selenite above 0.50 mg/kg did not negatively influence egg production and quail performance during the study time (10-20 weeks of age). Additionally, there was no adverse effect of sodium-selenite up to 1 mg/kg diet on the appetite, as indicated by similar feed intake among all groups.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…Previous authors considered that the use of high inorganic selenium doses in the diet of quails be limited due to the possible toxic effects. (13) However, our results showed that an amount of sodium-selenite above 0.50 mg/kg did not negatively influence egg production and quail performance during the study time (10-20 weeks of age). Additionally, there was no adverse effect of sodium-selenite up to 1 mg/kg diet on the appetite, as indicated by similar feed intake among all groups.…”
Section: Discussioncontrasting
confidence: 49%
“…Lower levels have been associated with the development of cardiovascular disease, impaired growth and development, poor feathering, reduce egg production, susceptibility to viral infections, and an increased risk of mortality. (13) However, all our experimental animals were alive and apparently healthy at the end of the study, even quails fed the control diet without supplementation (0.1 mg/kg of selenium), as shown in Table 1. Surai et al (8) proposed that the ingredients of poultry diets have variable selenium content, and perhaps this content is adequate to satisfy the requirements of laying quails.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations